New insights into the stability and structural evolution of some gold nanoclusters. Issue 2 (20th December 2016) - Liu, Liren; Yuan, Jinyun; Cheng, Longjiu; Yang, Jinlong
Abstract : Understanding the stability and structural patterns of some gold nanoclusters with a hybrid superatom network model and Au13 topological rule. Abstract : Revealing the stability and structural patterns is important for precisely synthesizing or assembling ligand protected nanoclusters, and even their applications as functional nanomaterials. Investigations on structural evolutional patterns and structural stability are very challenging, because structures change with the nanocluster size and the structural stability depends on both the electron structures of cores and ligand type. Herein, we propose a hybrid superatom network ( h SAN) model to understand the stability of some gold nanoclusters with different kinds of ligands. In this model, 4c-2e superatom Au4 can form conjugated superatom networks by vertex sharing, and ligands further connect the conjugated superatom networks together to form a bigger complex network, i.e. a h SAN. The stability of the clusters, including [Au24 (CCPh)14 (PPh3 )4 ] 2+, Au28 (S-c-C6 H11 )20, Au36 (SCH2 Ph- t Bu)8 Cl20, Au40 ( O -MBT)24 and Au52 (TBBT)32 can be explained uniformly by the h SAN model. Beyond that, a new heuristic structural pattern named the Au13 topological rule is proposed. In the light of this heuristic rule, every Au7 bi-tetrahedral kernel is included in an Au13 structure with quasi- O h symmetry, i.e. as long as the Au7 bi-tetrahedral kernel is formed, it will be surrounded by six Au atoms to form an Au13 structure topologically. According to this understanding, a new nanocluster [Au44 (CCH3 )26 (PCH3 )4 ] 2+ and a new nanowire with the structural evolutional formula [Au(20 n +4) (CCH3 )(12 n +2) (PCH3 )4 ] 2+ ( n = 1, 2, 3, 4, …) are predicted. Both the understanding of the stability and the structure rule are free from the type of ligand, and will be useful for the structural predictions and determinations of ligand protected gold nanoclusters.